Location specific recommendations on fertilizer application with RiceAdvice Lite in Mali. - Ahouanton, K.; Kone, P.; Guindo, S.; Dossou-Yovo, E.R. (2025)
"Rice production is a cornerstone of food security and rural livelihoods in Mali, yet farmers face persistent challenges such as soil nutrient depletion, erratic rainfall, and suboptimal fertilizer use. These constraints, combined with the lack of precise, localized guidance on fertilization, hinder productivity and sustainable land management. Providing farmers with location-specific fertilizer recommendations is therefore critical for optimizing nutrient use, increasing yields, reducing input costs, and minimizing environmental impacts. To address this need, the RiceAdvice Lite digital tool, a simplified and user-friendly version of the AfricaRice RiceAdvice platform, was deployed in 2025. RiceAdvice Lite integrates soil, weather, and agronomic data to deliver tailored recommendations on fertilizer type, rate, timing, and crop management practices. Its simplified interface, faster processing, and reduced technical requirements make it particularly suitable for smallholder farmers and extension agents. The tool was disseminated in key rice-producing regions, including Sikasso, Segou, and Koulikoro, through training of 18 extension technicians (5 women) who then supported farmers in adopting the recommendations. A total of 56,744 farmers (32% women) covering 31,209 hectares received location-specific guidance on nitrogen, phosphorus, and potassium application aligned with crop growth stages and local weather conditions. The adoption of RiceAdvice Lite recommendations led to significant impacts: average rice yields increased from 3.3 t/ha under farmers’ usual practices to 4.0 t/ha, representing a 23% improvement. Fertilizer use efficiency also improved markedly, with partial productivity gains for N (41 vs. 35 kg grain/kg N), P (381 vs. 97 kg grain/kg P), and K (250 vs. 97 kg grain/kg K). Farmers incomes increased by 35%, from USD 564/ha to USD 761/ha. These results demonstrate that RiceAdvice Lite is an effective tool for promoting precision agriculture in Mali, supporting sustainable fertilizer management, improving yields, and enhancing farmers’ livelihoods. The experience highlights the potential of simplified digital decision-support tools to scale climate-smart and data-driven agricultural practices in diverse agroecological contexts. "